Legal Review of Violations of the Code of Ethics by Notaries in the Preparation of Share Sale and Purchase Deeds (Study of Supreme Court Decision Number 15k/Pid/2020) - Fitria Almaida, Ade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
A notary is a public official authorized to make authentic deeds as evidence with perfect evidentiary force and is required to carry out his/her duties professionally, with integrity, and in compliance with the code of ethics. However, in practice, violations of the code of ethics still occur, resulting in criminal acts, as stipulated in Supreme Court Decision Number 15K/Pid/2020. Therefore, this study analyzes the legal responsibility of notaries and the legal consequences of authentic deeds made. This study uses a normative juridical method with a statutory and case approach, based on secondary data analyzed prescriptively to assess the suitability of the application of the law with legal norms and principles. The results of the study indicate that notaries can be held accountable for ethical, administrative, civil, and criminal matters, and authentic deeds containing false information can lose their evidentiary force, so supervision and preventive-repressive efforts are needed.